2016
DOI: 10.1002/2016gl070716
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of CO2 dynamics and air‐water fluxes in a river‐dominated estuary and a mangrove‐dominated marine estuary

Abstract: The fugacity of CO2 (fCO2 (water)) and air‐water CO2 flux were compared between a river‐dominated anthropogenically disturbed open estuary, the Hugli, and a comparatively pristine mangrove‐dominated semiclosed marine estuary, the Matla, on the east coast of India. Annual mean salinity of the Hugli Estuary (≈7.1) was much less compared to the Matla Estuary (≈20.0). All the stations of the Hugli Estuary were highly supersaturated with CO2 (annual mean ~ 2200 µatm), whereas the Matla was marginally oversaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 56 publications
(83 reference statements)
8
44
0
Order By: Relevance
“…Hence, the metabolic balance of a given estuary is closely linked to the hydrology of its watershed. This idea is supported by previous findings linking seasonal to annual variation in CO 2 flux with changes in freshwater delivery, through both surface (Akhand et al, 2016;Drupp et al, 2011;Flecha et al, 2015;Guo et al, 2009;Yao et al, 2007;Zhai et al, 2005) and groundwater channels (Call et al, 2015;Jeffrey et al, 2016;Macklin et al, 2014;Santos et al, 2010). Watershed-scale hydrology may also drive complex changes in the buffering capacity of estuarine waters, impacting calcifying organisms (Barton et al, 2012;Hofmann et al, 2010), pH-sensitive processes like nitrification (Beman et al, 2010;Huesemann et al, 2002), and even animal behavior (Dodd et al, 2015;Leung et al, 2015).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Hence, the metabolic balance of a given estuary is closely linked to the hydrology of its watershed. This idea is supported by previous findings linking seasonal to annual variation in CO 2 flux with changes in freshwater delivery, through both surface (Akhand et al, 2016;Drupp et al, 2011;Flecha et al, 2015;Guo et al, 2009;Yao et al, 2007;Zhai et al, 2005) and groundwater channels (Call et al, 2015;Jeffrey et al, 2016;Macklin et al, 2014;Santos et al, 2010). Watershed-scale hydrology may also drive complex changes in the buffering capacity of estuarine waters, impacting calcifying organisms (Barton et al, 2012;Hofmann et al, 2010), pH-sensitive processes like nitrification (Beman et al, 2010;Huesemann et al, 2002), and even animal behavior (Dodd et al, 2015;Leung et al, 2015).…”
Section: Introductionsupporting
confidence: 71%
“…While submarine groundwater discharge may be a significant DIC source in some estuaries (Call et al, ; Macklin et al, ; Santos et al, ), this source has been determined to be small in both the NeuseRE (Fear et al, ; Null et al, ) and NewRE (Crosswell et al, ). Previous studies have identified river‐dominated estuaries as large CO 2 sources, relative to marine‐dominated ones (Akhand et al, ; Jiang et al, ). Our findings support this understanding; we show that river‐borne CO 2 ([CO 2 ] river ) was indeed larger in the river‐dominated NeuseRE than in the marine‐dominated NewRE, by a factor of 2.6–5.2.…”
Section: Discussionmentioning
confidence: 99%
“…Different aspects of C cycling in the Hooghly-Sundarbans system have been reported by Ray et al (2015Ray et al ( , 2018. Barring Samanta et al (2015), which has wider spatial and temporal coverages with respect to DIC in the Hooghly, other studies are severely limited in spatial coverage with focus on the middle to lower parts of the Hooghly estuary and a few locations in the Sundarbans (one location by Ray et al, 2015Ray et al, , 2018; three locations by Akhand et al, 2016). Given the vast expanse of these estuaries, the extrapolation of data Ghosh, (1973), Khan (1995) No information available Dissolved metal flux Increased from 230 % to 1770 % annually Samanta and Dalai (2018) No information available from these studies for the entire ecosystem may lead to overestimation and underestimation.…”
mentioning
confidence: 98%
“…Earlier, the major focus of biogeochemical studies in the Hooghly and the estuaries of the Sundarbans had been on the biogeochemistry of trace gases (Mukhopadhyay et al, 2002;Biswas et al, 2004Biswas et al, , 2007Ganguly et al, 2008Ganguly et al, , 2009Dutta et al, 2013Dutta et al, , 2015Dutta et al, , 2017 with the exception of one comprehensive study on nutrient budgets at the Hooghly estuary (Mukhopadhyay et al, 2006). Recently, attempts have been made to understand different aspects of C cycling in these two estuaries (Samanta et al, 2015;Ray et al, 2015Ray et al, , 2018Akhand et al, 2016). Samanta et al (2015) comprehensively studied DIC dynamics in the Hooghly estuary, whereas Akhand et al (2016) focused on DIC and pCO 2 at the Hooghly-Matla estuary.…”
mentioning
confidence: 99%
See 1 more Smart Citation